Lipocalin 2 Is a Regulator During Macrophage Polarization Induced by Soluble Worm Antigens - Shen, Hanyu; Wang, Ziheng; Huang, Ailong; Zhu, Dandan; Sun, Pingping; Duan, Yinong (Frontiers in Cellular and Infection Microbiology, 2021)
Caused by schistosomes, the human schistosomiasis is a tropical zoonotic parasitic disease. Pathologically, it occurs most often in the intestines and the liver, as the sites of Schistosoma japonicum eggs accumulation. The parasites' produce eggs cause the main pathology in patients Deposited parasite eggs in the liver induces the production of multiple cytokines that mediate the immune response, which in turn leads to granulomatous responses and liver fibrosis. These impacts on the hosts’ quality of life and health status, resulting in severe morbidity and even mortality. In this study, microarray analysis was conducted on the analysis of differentially expressed genes (DEGs) between ordinary samples and those obtained from three distinct mice for 6- week group by using limma package. In total, we excavated the differential expression LCN2 was exhibited high expressions profile in GSE59276, GSE61376 demonstrated the result. Furthermore, immune cell infiltration results by using CIBERSORT suggested that detailed analysis of the immune subtype distribution pattern. In vivo experiments like Real-time quantitative PCR, immunohistochemical (IHC) staining and Immunofluorescence (IF) demonstrated the expressions of LCN2 was significantly up- regulated in S. japonicum infected mice liver tissues and located in macrophages. Previous studies have shown that macrophages act as the first line of defense during schistosome infection and are an important part of liver granuloma. We used S. japonicum soluble worm antigens (SWA) to induced RAW264.7 cells to construct an in vitro inflammatory model. The current study aimed to investigate whether the NF-κB signaling network is involved in LCN2 upregulation induced by SWA and whether LCN2 can promote M1 polarization of macrophages under SWA treatment. Our research work suggests that LCN2 is significant in the development of early infection caused by S. japonicum and is of great value for further exploration. Collectively the findings indicated that SWA promoted the expression of LCN2 and promoted M1 polarization of macrophages via the upregulation of NF-κB signaling pathway. Our findings demonstrate that NF-κB /LCN2 is necessary for migration and phagocytosis of M1 macrophages in response to SWA infection. Our study highlights the essential role of NF-κB/LCN2 in early innate immune response to infection.